Cockpit learning in power distant cockpits: The interaction effect of pilot's interdependence and inclination to teamwork in airline industry. (January 2015) - Alam, Muhammad Aftab
Abstract: Cockpit learning is an essential feature of flying profession, but it may be hampered by power distance in the cockpit due to captain/co-pilot subordination. Speaking-up to the captain may be difficult for some co-pilots but not speaking-up resulted in numerous aircraft accidents. This research examines cockpit learning among airline pilots and assumes that power distance reduces cockpit learning whereas pilot's interdependence and pilot's inclination towards teamwork can counter balance it. The study develops a short cockpit-learning-scale and validates it through a stratified sample of 231 pilots chosen from British Airways, Pakistan International Airline and Saudi Arabian Airline. Data analysis indicated a strong negative influence of power distance on cockpit learning, and significant interaction effect of pilot's interdependence and pilot's inclination towards teamwork. Together, the findings suggest that pilot's interdependence and inclination towards teamwork significantly minimize the negative influence of power distance on cockpit learning.